2017
DOI: 10.1016/j.msea.2017.08.086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forging on the low cycle fatigue behavior of cast AZ31B alloy

Abstract: The effect of forging on the low cycle fatigue (LCF) behavior of cast AZ31B was investigated.The forging process was conducted at a temperature of 450°C and speed of 390mm/min. Fully reversed (R ε =-1) strain controlled cyclic tests were performed on as-cast and forged materials under total strain amplitudes of 0.1%-1.2%. Forging eliminated the dendritic morphology and reduced β-phase intermetallics observed in the cast alloy. Additionally sharp basal texture and bimodal grain structure were developed. General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 65 publications
(83 reference statements)
4
21
0
Order By: Relevance
“…The tension and compression behavior as well as fatigue properties of forged AZ31 were investigated by Toscano et al [65,66]. As-cast stock material was homogenized at 450 • C for 3 h and formed directly afterwards.…”
Section: Az31mentioning
confidence: 99%
“…The tension and compression behavior as well as fatigue properties of forged AZ31 were investigated by Toscano et al [65,66]. As-cast stock material was homogenized at 450 • C for 3 h and formed directly afterwards.…”
Section: Az31mentioning
confidence: 99%
“…These residual twins can affect the fatigue response of the alloy in two ways. First, the interactions between the twin-twin bands and also twin-dislocations can lead to the crack initiation causing premature failure [14] [28]. Alternatively, some studies have suggested that the extension twinning can elongate the fatigue life in the light of crack growth retardation due to the roughness-induced crack closure [29].…”
Section: Fatigue Behaviourmentioning
confidence: 99%
“…Recently, intensive research and development work has been conducted in both academic and industrial institutes to develop advanced materials processing and surface treatment technologies for replacing aluminum using Mg alloys in the design and manufacture of fatigue‐critical automotive components, such as the control arm . Three grades of Mg alloy (i.e., AZ31B, AZ80, and ZK60) were selected as the candidate materials for the development of cost‐effective forging processes for the fabrication of a lower control arm, due to their superior mechanical properties and excellent forgeability .…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the corrosion properties of as‐cast AZ31B, AZ80, and ZK60 alloys with and without MAO coatings have been investigated using advanced electrochemical and salt spray testing methods. The cast Mg alloys were used as the starting materials for development of the lower control arm . On the basis of the results of the corrosion properties of cast alloys, the corrosion and corrosion fatigue performances of the forged Mg alloys with and without coatings will be investigated in the follow‐up experiments.…”
Section: Introductionmentioning
confidence: 99%